Қазақстан Республикасында конституциялық заңдылықты нығайтудағы конституцияның жоғарылығының маңызы (Journal of actual problems of jurisprudence, 2019)
The article deals with the content and essence, guarantee the rule of the Constitution, examines the need to improve the consistentconstitutional control in the Republic of Kazakhstan, the analysis of the need to eliminate the contradictions in the study of problemsof rule of the Constitution.